Pengaruh Macam Pupuk Organik Cair terhadap Pertumbuhan dan Hasil Tiga Varietas Tanaman Pakcoy (Brassica rapa L.) - Winata, Brama Sukma; Supandji, Supandji; Rahardjo, Tjatur Prijo; Nareswari, Aptika Hana Prastiwi; Probojati, Rasyadan Taufiq (Universitas Kadiri, 2025)
Brassica rapa L., a member of the mustard green family, is a high-value crop with notable economic potential and nutritional benefits in Indonesia. Within the Brassicaceae family, commonly cultivated mustard varieties, such as mustard green, white mustard, and pakcoy, exhibit distinct differences in morphology and characteristics. Pakchoy is especially prized for its health benefits, primarily attributed to its dietary fiber content, which aids digestion and binds bile acids, reducing cholesterol levels. This study evaluated the effects of various liquid organic fertilizers (LOF) and pakchoy varieties on plant growth and yield. The research utilized a factorial Complete Randomized Design (CRD) with two main factors. The first factor was three types of LOF: rice water (L1), coconut water (L2), and banana stem (L3). The second factor consisted of three pakchoy varieties: Nauli (V1), Masbro (V2), and Gardena (V3). Observed parameters included plant height, leaf count, fresh weight, root count, and root length, recorded at 7, 14, 21, and 28 days after planting (DAP). Data were analyzed using ANOVA, with significant differences further tested by LSD at a 5% significance level. The results demonstrated that the rice water LOF (L1) combination and the Nauli variety (V1) produced the best outcomes across all growth parameters. These findings highlight the effectiveness of using rice water LOF alongside the Nauli variety as an optimized approach to improving pakcoy growth, yield, and overall agricultural productivity. Tanaman sawi, khususnya pakcoy (Brassica rapa L.), memiliki nilai ekonomi dan gizi yang tinggi di Indonesia. Dalam keluarga Brassicaceae, jenis-jenis sawi seperti sawi hijau, sawi putih, dan sawi pakcoy memiliki perbedaan mencolok pada morfologi dan karakteristik lainnya. Pakcoy dikenal karena manfaat kesehatannya, terutama kandungan serat yang dapat mempercepat proses pencernaan dna mengikat asam empedu penyebab kolesterol. Penelitian ini bertujuan untuk mengevaluasi pengaruh variasi pupuk organik cair (POC) dan jenis varietas pakcoy terhadap pertumbuhan serta hasil tanaman. Penelitian dilakukan menggunakan Rancangan Acak Lengkap (RAL) faktorial dengan dua faktor, jenis pupuk cair (POC air beras, POC air kelapa, dan POC bonggol pisang) dan varietas pakcoy (Nauli, Masbro, dan Gardena). Parameter yang diamati meliputi tinggi tanaman, jumlah daun, berat segar, jumlah akar, dan panjang akar. Pengamatan dilakukan pada umur 7,14, 21, dan 28 hari setelah tanam (HST), dan data dianalisis menggunakan ANOVA. Perbedaan signifikan diuji dengan Beda Nyata Terkecil (BNT) pada taraf5%. Hasil penelitian menunjukkan bahwa kombinasi POC air beras dengan varietas Nauli memberikan hasil terbaik dalam mendukung pertumbuhan pakcoy. Kombinasi ini menghasilkan nilai optimal pada seluruh parameter, seperti tinggi tanaman, jumlah daun, dan berat segar. Temuan ini menunjukkan potensi penggunaan POC air beras dengan varietas Nauli sebagai kombinasi efektif untuk meningkatkan produktivitas tanaman pakcoy di Indonesia.